Examining the Impacts of Dividend Payout and Share Repurchase to Future Firm Performance: Evidence from Malaysian Public Listed Firms - Chee Ling, Chin (UNIMAS, 2023)
Signaling theory is built on the premise that information asymmetry exists between managers and investors. The information content hypothesis, also known as the information signaling hypothesis, contends that corporate payout policy functions as a signaling tool to reflect an optimistic view of firm prospects to investors. Nevertheless, the action of payout has long been criticized for sending weak signals that mislead investors through price manipulation. Therefore, this study intends to investigate the information content of corporate payout policy in Malaysia by examining the impacts of dividend payout and share repurchase on future firm performance. This study is conducted within the sample period of 2000 to 2020, with the sample data comprising 355 dividend paying firms, 153 share repurchasing firms and 144 mutual payers listed on Bursa Malaysia. Panel data regression analysis is conducted to investigate the influence of the respective payout policy on future firm performance as represented by the proxies of earnings per share, earnings yield, return on assets, return on equity, operating income and operating cash flow measured in the following year of payout. The results from the fixed effect model show a positive and significant relationship between share repurchase ratio and all proxies of future firm performance, which supports the information signaling hypothesis. In addition, the predictive ability of share repurchases on future firm performance is also proven among subsamples of share repurchasing firms with small market capitalization and high payout frequency. On the other hand, the results from the fixed effect model show an insignificant relationship between dividend ratio and all proxies of future firm performance, which rejects the information content hypothesis. However, the predictive power of dividends on future firm performance is observed among subsamples of dividend paying firms with large market capitalization and regular dividend payments. Meanwhile, the total payout ratio for mutual payers is only positively and significantly related to future return on assets and future operating income. Overall, the results suggest that corporate payout policy does indeed convey valuable information about future profitability among Malaysian public listed firms. The real earnings improvement demonstrated in the current study thus resolves the issue of false market signals originating from dividends and share repurchases.